Mycobacterium tuberculosis Strains Lacking Surface Lipid Phthiocerol Dimycocerosate Are Susceptible to Killing by an Early Innate Host Response - Day, Tracey A. (Infect Immun, 2014)
The innate immune response plays an important but unknown role in host defense against Mycobacterium tuberculosis. To define the function of innate immunity during tuberculosis, we evaluated M. tuberculosis replication dynamics during murine infection. Our data show that the early pulmonary innate immune response limits M. tuberculosis replication in a MyD88-dependent manner. Strikingly, we found that little M. tuberculosis cell death occurs during the first 2 weeks of infection. In contrast, M. tuberculosis cells deficient in the surface lipid phthiocerol dimycocerosate (PDIM) exhibited significant death rates, and consequently, total bacterial numbers were reduced. Host restriction of PDIM-deficient M. tuberculosis was not alleviated by the absence of interferon gamma (IFN-γ), inducible nitric oxide synthase (iNOS), or the phagocyte oxidase subunit p47. Taken together, these data indicate that PDIM protects M. tuberculosis from an early innate host response that is independent of IFN-γ, reactive nitrogen intermediates, and reactive oxygen species. By employing a pathogen replication tracking tool to evaluate M. tuberculosis replication and death during infection, we identify both host and pathogen factors affecting the outcome of infection.